15. THERAPEUTIC OUTCOMES OF AURICULAR ACUPRESSURE COMBINED WITH “AN THAN” HERBAL PILL IN THE TREATMENT OF PRIMARY INSOMNIA PATIENTS (Vietnam Journal of Community Medicine, 2025)
Objective: This study aimed to evaluate the clinical effectiveness of combining auricular acupressure with “An Than” herbal pills in the treatment of primary insomnia patients categorized in Yin deficiency with excess heat pattern.Subjects and methods: A before - after clinical intervention study was conducted on 40 patients aged 18 and above, diagnosed with primary insomnia according to DSM-5 criteria. The intervention included auricular acupressure applied to five bilateral ear points (replaced every 5 days) and “An Than” herbal pills taken twice daily for 20 consecutive days. Clinical outcomes were assessed using the ISI, sleep onset latency, total sleep duration, and sleep efficiency.Results: After 20 days of treatment, the mean ISI score decreased by 7,6 points (p < 0,05); sleep onset latency shortened from 81,00 ± 7,44 minutes to 36,00 ± 10,08 minutes; total sleep time increased by 1,19 ± 0,52 hours; and sleep efficiency improved from 56,31% to 74,60%.Conclusion: The combined use of auricular acupressure and “An thần” pills demonstrates significant efficacy in improving sleep quality and reducing insomnia symptoms in patients categorized in Yin deficiency with excess heat.
Keywords: Primary insomnia; auricular acupressure; “An Than” herbal pill.